Community Structure of Bivalves in Seagrass Bed Ecosystem of Penyengat Island, Tanjungpinang City Riau Islands Province - Yasir Muammar Lubis; Syafruddin Nasution; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe study was conducted in Penyengat Island in June 2014, Tanjungpinang City, Riau Islands Province. The Penyengat Island coastal is known as fishing area and as cruise line and this island has seagrasses ecosystem. The research aim was to determine the structure of bivalves and its relationship with seagrass density by using the survey method. There were 3 station choser each station were 3 placed line transects, and each transects have 3 plot with the area of 1 x 1 m². The resulsts of the study showed there were 8 species of bivalves from 5 famalies and 6 genus. The species were concisting of Meritrix meritrix, Mercenaria mercenaria, Pina bicolor, A granosa, A inflate, Barbatia bistrigata, Crassostrea gasar and Placuna placenta. There were two species of seagrasses identified, i. e. Enhalus acoroides, and Halophila ovalis. Based on simple regression analysis it was concluded that the relationship between the density of seagrass density and bivalves population had a very weak correlation (r = 0,06).Keywords: Penyengat Island, Bivalves, Seagrass, Community structure